The Effectiveness of Fabric Safeguards in Protecting and Improving the Indonesian Textile Industry Competitiveness - Nurkomariyah, Siti; Tyasti, Avia Enggar (Jurnal Manajemen & Agribisnis, 2022)
This study investigates the effectiveness of fabric safeguards set by the Indonesian government on protecting and improving the competitiveness of the textile industry in the domestic and global markets. Data on exports and imports of 107 HS codes of fabrics subject to additional import duties in 2011-2020 are used to measure Indonesia's competitiveness compared with six major exporting countries. The Revealed Comparative Advantage (RCA) and the Trade Specialization Index (TSI) interpret the Indonesian fabric competitiveness and its competitors. Independent variables of this research are Safeguard Measure Import Duty (BMTP), Most Favoured Nation (MFN) rates, period of investigation, exchange rate, and inflation. The results show that the safeguard, MFN, and period of investigation significantly affect the decline in fabric imports, but other variables have no significant effect. The regime effectively protects Indonesia's textile industry, which is marked by a decrease in the value and volume of imports during the validity period. The RCA indicates that Indonesia does not have a comparative advantage, and according to the TSI, Indonesia is an importing country. BMTP cannot change Indonesia's position as a net exporter and improve its competitiveness. This study implies that it is necessary to increase investment in more efficient production machines with high productivity, optimize the supply chain, reduce production and enterprise costs, and restructure business models; thus, their competitiveness increases in domestic and foreign markets. Keywords: BMTP, fabric, comparative advantage, trade index, impor duties